ANALYSIS OF THE ACCEPTABILITY AND NUTRITIONAL CONTENT OF CHICKEN NUGGETS WITH THE ADDITION OF TEMPE AND EGGSHELL FLOUR AS AN ALTERNATIVE SNACK FOR SCHOOL CHILDREN. - Jerry Kristiady (Journal of Global Nutrition, 2023)
School children's snack food needs to be considered because it plays an important role in providing the nutrients needed by school-age children, especially protein and calcium. Tempe is a vegetable product that can increase protein intake and has potential as a functional food. Chicken egg shells are a source of calcium that has not been utilized optimally and can be used as an additive in processed products to increase calcium content. Chicken nuggets with the addition of tempeand eggshell flour can be recommended as an alternative snack for school children which contains good nutrition. Objective: To find out the acceptability and nutritional content of chicken nuggets with the addition of tempe and egg shell flour as an alternative to school children's snacksResearch methods: This study used an experimental research design consisting of three treatments (F1, F2, F3). The test was carried out in 2 stages, namely the organoleptic test to see the level of preference of the panelists for the nuggets and the test for the nutritional content of the nuggets, namely protein, carbohydrates and calcium. Results: The results showed that the most preferred chicken nugget in terms of color, aroma and taste was the F3 formula. Chicken nuggets in the best treatment had protein (30.61%) carbohydrates (15.21%) and calcium (8mg). These chicken nuggets can be used as an alternative for school children.